(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Аннотация. Статья посвящена исследованию факторов, обуславливающих культурные различия при переводе, и их влиянию на качество и точность перевода. В работе рассматриваются ключевые аспекты, включая лингвистические, исторические и социальные контексты, которые играют решающую роль в интерпретации текста на целевом языке. Использован сравнительно-сопоставительный и аналитический методы для выявления наиболее значимых причин культурных расхождений. Полученные результаты подчеркивают необходимость учета межкультурных факторов при адаптации текстов, а также значимость компетенций переводчика для минимизации ошибок и искажений. Выводы работы направлены на расширение теоретической базы переводоведения и предоставляют практические рекомендации для специалистов в области перевода. Abstract. The article is devoted to the study of the factors that cause cultural differences in translation, and their impact on the quality and accuracy of translation. The paper examines key aspects, including linguistic, historical and social contexts, which play a crucial role in interpreting the text in the target language. Comparative and analytical methods were used to identify the most significant causes of cultural differences. The results obtained emphasize the need to take into account cross-cultural factors when adapting texts, as well as the importance of translator's competencies to minimize errors and distortions. The conclusions of the work are aimed at expanding the theoretical base of translation studies and provide practical recommendations for specialists in the field of translation.